A study of critical thinking in higher education students - Yasaldez Eder Loaiza Zuluaga; Gloria Matilde Gil Duque; Fabián Andrés David Narváez (Universidad de Caldas, 2020)
The study shows a proposal on specific diagnosis of critical thinking skills in higher education students according to literal, inferential and critical reading levels. A literature review on Critical thinking was done to support concepts. This proposal is adapted from the variables of the information obtained. One of the conclusions shows that the career profile is a determining factor in the result and that motivation and interest are outstanding in the reading and writing processes. Teaching students to evaluate their own processes and helping teachers to include critical readings in their curricula will help to develop effective skills associated with critical thinking. The general objective of the research project is to strengthen Critical Thinking and the argumentative capacity of the students of the schools of Administration, Health Sciences, Engineering and Architecture, Social Sciences, Humanities and Theology through strategies of reading and writing. A mixed methodology was used; the researches designed and administered 2 critical reading texts, each with 10 questions and organized in 3 reading levels (literal,inferential and critical), to 158 students; then, a data analysis on how students infer, interpret and analyze text content before they start a communicative course was done. The results show that according to the professional profile, some students are more argumentative that others and that students lack Critical Thinking skills.